2014
DOI: 10.2485/jhtb.23.407
|View full text |Cite
|
Sign up to set email alerts
|

Stainless and Titanium Fibers as Non-degradable Three-dimensional Scaffolds for Bone Reconstruction

Abstract: Stainless steel is used for various medical devices. Titanium is also widely used because of its tight bonding to bone tissue, namely osseointegration. The aim of the present study was to investigate the efficacy of three-dimensional stainless steel and titanium porous structure scaffolds by in vitro and in vivo experiments. Stainless steel and titanium fiber materials were designed as non-degradable metallic three-dimensional scaffolds with a three-dimensional porous structure for bone reconstruction. In one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In addition to Kokubo's SBF, Hanawa et al [5,6] proposed Hanks' balanced salt solution (HBSS) without organic species at pH 7.4 as an SBF and found apatite formation on a Ti surface in HBSS. Our group [7][8][9][10] examined apatite deposition on the surface of modified Ti materials, such as thin-apatite-coated or DNA-coated Ti materials, after immersion in SBF and found that better apatite deposition on the biomaterials in HBSS corresponded with better in vivo bone formation. Thus, an SBF immersion experiment is useful for evaluating biocompatibility or tissue responses of biomaterials for hard tissue, which can reduce the number of animals used and the duration of animal experiments.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Kokubo's SBF, Hanawa et al [5,6] proposed Hanks' balanced salt solution (HBSS) without organic species at pH 7.4 as an SBF and found apatite formation on a Ti surface in HBSS. Our group [7][8][9][10] examined apatite deposition on the surface of modified Ti materials, such as thin-apatite-coated or DNA-coated Ti materials, after immersion in SBF and found that better apatite deposition on the biomaterials in HBSS corresponded with better in vivo bone formation. Thus, an SBF immersion experiment is useful for evaluating biocompatibility or tissue responses of biomaterials for hard tissue, which can reduce the number of animals used and the duration of animal experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The tibia of the rabbit was shaved and disinfected with 10% povidone-iodine solution. After anaesthetic and disinfection procedures, a flap was raised, and three bone defects of 3 mm in depth and 3 mm in diameter were drilled in each tibia in imitation of the similar study on the bone scaffolds fabricated by Ti fibre [ 14 ]. The bone defects were randomly designated to the specimen from the three porosities ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the development of artificial bone substitutes using synthetic materials has emerged as a viable alternative. Metals such as titanium, stainless steel, or chromium alloys have been widely used due to their high mechanical strength, wear resistance, and durability [62,63]. However, the non-biodegradable nature of metal implants may require secondary surgery for removal, and their mechanical properties may not match those of the surrounding bone, leading to stress shielding and subsequent bone resorption [64][65][66][67].…”
Section: Conventional Strategies For Vascularized Bone Tissue Enginee...mentioning
confidence: 99%